Identification of SER-653-ASN mutation conferring resistance to imidazolinone in Malaysian weedy rice - Ahmad Hamdani, Muhammad Saiful; Zakaria, Norazua; Jamil, Mohammad Azizi (Brazilian Weed Science Society, 2024)
Background: The prevalence of weedy rice infestation has been shown to cause a significant reduction in Malaysian rice yield. The introduction of the Clearfield© Production System has significantly reduce weedy rice infestation, but its mismanagement has led to an increase in imidazolinone-resistant weedy rice. Objective: This study aims to investigate the resistance levels and patterns of weedy rice and to identify possible causes of resistance. Methods: The putative imidazolinone-resistant and susceptible weedy rice were collected in two different rice fields in Kelantan, Malaysia. A petri dish seed bioassay and whole-plant dose-response studies were conducted using three imidazolinone herbicides at seven rates. Surviving plants underwent molecular DNA extraction, nucleotide sequencing, and in vitro acetohydroxy acid synthase (AHAS) inhibition assay studies. Results: The putative imidazolinone-resistant weedy rice was found to be resistant to all three imidazolinone herbicides at the recommended field rate. Further confirmation by DNA sequencing revealed a Ser-653-Asn mutation in all resistant populations. In vitro AHAS inhibition assays confirmed imidazolinone resistance at the enzymatic level. Conclusion: The weedy rice population on the eastern coast of Peninsular Malaysia is resistant to imidazolinone herbicides. The Ser-653-Asn mutation was detected and is known to be the primary cause of imidazolinone resistance in this population of weedy rice.